The theory of equilibrium magnetic properties of the granulated magnetic materials - Stefanovskii, E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2000)
The present-day analysis of the theoretical adaptation status of the experimental curves of the magnetization and the static magnetic susceptibility as the functions of external parameters H and T ( H is an applied external magnetic field and T is a temperature) is made for granulated ferromagnetic systems. Once more it is pointed that the consideration of the energy of magnetic anisotropy of a ferromagnetic material (as against the methods of the adapt used everywhere) play an essential role for the understanding of the magnetic behavior of the above systems mentioned and allow us to investigate the magnetoanisotropic behavior of granulated magnetic systems [at the certain granule distribution functions (by their volume and orientation) as regards the external magnetic field]. It is shown that the use of the &quotblocking&quot concept is not necessary for the investigations of the thermodynamically equilibrium magnetic properties of the above systems.